Trade, foreign direct investment, and pollution abatement - Shruti Sharma (Asian Development Bank Institute (ADBI), 2019)
This paper analyzes the impact of tariff liberalization and foreign direct investment on pollution from a plant-level perspective. It considers how globalization impacts plant-level investment in pollution abatement expenditure. Popular hypotheses on trade and pollution cite the pollution haven effect - that trade leads to a worsening of environmental conditions in developing countries. By analyzing the differential impact of input and output tariff liberalization, however, this paper finds that input tariff liberalization actually induces plants to invest more in pollution abatement equipment. Further, it finds that an increase in competition through output tariff liberalization does not in fact lead to a decline in spending on pollution control equipment in order to cut costs, as some theories might suggest. Further, it also finds a positive impact of increased inflows of foreign direct investment on spending in pollution control equipment, arguably through access to cleaner foreign technology. These effects are mainly driven by states that are newly emerging as the main attractions for foreign direct investment.
Keywords: Q52; F61; F64; F18; 330; pollution control capital; input tariffs; foreign direct investment; plant heterogeneity; India